The perception towards national anti-smoking initiatives among Malay male smokers - Ismail, Suriani; Juni, Muhamad Hanafiah; K. C. Mani, Kulanthayan; Saliluddin, Muhamad Suhainizam; Zakwan, Raja Ahmad; Tiong, Ling Rong (Tehran University of Medical Sciences, 2014)
Background: Global Adult Tobacco Survey (GATS), Malaysia 2011 reported that the prevalence of smoking was highest among Malays male i.e., 24.6% (CI:22.1,27.3). The aim of this study was to evaluate the perception of a group of smokers towards various national anti-smoking initiatives as well as its association with age and education level.